IMPACT OF FINANCIAL REPORTING QUALITY ON INVESTMENT EFFICIENCY: AN APPLICATION IN ISTANBUL STOCK EXCHANGE - Selim CENGİZ; Yusuf DİNÇ; Büşra TOSUNOĞLU (International Journal of Eurasia Social Sciences, 2017)
Financial reporting is one of the most important outputs of the accounting information system that provide necessary information to make a economic desicion and evaluation of profitability and performance of enterprises. On the other hand, financial reporting quality includes the accuracy of reported information to better identify the activities of the companies. Pratically investors wants to get information about cash flow of company’s which will invest. Trustworthy financial reporting information is an element that helps managers to make invesment desicion. Financial reporting quality can increase investment efficiency by reducing information asymmetry. In many previous studies, it has been found that financial reporting qualifications increase the investment efficiency. In this context The aim of paper is to determine impact of financial reporting quality on investment efficiency. In accordance with this purpose, the data for 70 companies operating in the manufacturing industry in BIST (Istanbul Stock Exchange) are utilized from between the years 2010-2014. As dependent variable in this research, investment efficiency is used and financial reporting quality is used as independent variable. In this study, panel data analysis panel regression analysis is conducted. In the result of analysis shows that there is a negative correlation between financial reporting quality and investment efficiency (for low or excessive investments.